1996
DOI: 10.1042/bj3200659
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the expression of stromelysin-2 by growth factors in keratinocytes: implications for normal and impaired wound healing

Abstract: Keratinocyte growth factor (KGF) has been implicated in wound re-epithelialization and branching morphogenesis of several organs. To determine whether KGF induces these effects via induction of matrix metalloproteinase expression we have analysed the effect of KGF on the expression of stromelysin-2 in cultured HaCaT keratinocytes. Here we show a strong induction of stromelysin-2 mRNA within 5-8 h of stimulation of these cells with KGF. The degree of induction was similar to that achieved by treatment with epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 27 publications
5
76
0
2
Order By: Relevance
“…Instead, gelatinase A protein did not colocalize with laminin-5 and apparently does not cleave laminin-5 during skin carcinogenesis. Interestingly, TGF-β1 is able to induce both MMP-10 (Madlener et al, 1996) and laminin-5 in keratinocytes (Kainulainen et al, 1998). Cultured human foreskin keratinocytes express MMP-10, while fibroblasts express MMP-3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, gelatinase A protein did not colocalize with laminin-5 and apparently does not cleave laminin-5 during skin carcinogenesis. Interestingly, TGF-β1 is able to induce both MMP-10 (Madlener et al, 1996) and laminin-5 in keratinocytes (Kainulainen et al, 1998). Cultured human foreskin keratinocytes express MMP-10, while fibroblasts express MMP-3.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown, that the expression of MMP-10 is induced by phorbol ester, TGF-α and epidermal growth factor (EGF) in normal epidermal keratinocytes and by KGF, EGF, TNF-α and TGF-β1 in HaCaT keratinocytes (Madlener et al, 1996). 43 cell lines established from primary and recurrent tumours and metastases of SCCs of the head and neck at the time of operation in the Turku University Central Hospital (Johansson et al, 1997b) were examined for basal expression of MMP-10.…”
Section: Regulation Of Mmp-10 Expression In Scc Cells In Culturementioning
confidence: 99%
See 1 more Smart Citation
“…MMP10-dependent processing of DMKN is of particular interest, because DMKN expression in skin wounds spatially and temporally overlaps with increased levels of MMP10 in wound edge keratinocytes (4,(73)(74)(75). Moreover, recombinant DMKN inhibited ERK phosphorylation in cultured keratinocytes and delayed wound closure in mice (75,76).…”
Section: Discussionmentioning
confidence: 99%
“…For these experiments, we used RNA isolated from quiescent and KGF-stimulated HaCaT keratinocytes. Genes identified so far encode, for example, nucleotide biosynthesis enzymes (Gassmann et al, 1999), which are required for proliferation, the estrogen-responsive B box protein (Beer et al, 2002), which initiates early differentiation, and stromelysin-2 (Madlener et al, 1996;Krampert et al, 2004), which regulates migration. Finally, the transcription factor Nrf2 (Braun et al, 2002;auf dem Keller et al, 2006) and the non-selenium glutathione peroxidase peroxiredoxin 6 (Frank et al, 1997) mediate protection of epithelial cells against cytotoxic agents such as reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%